Impact of Time Delay on Short Term Outcome of Primary Percutaneous Coronary Intervention (PCI) in Bangladeshi Population - Morshed, Md Golam; Azam, MG; Arefin, Md Minhaj; Hussain, Khondker Shaheed; Jahan, Jafrin; Ahmed, Nishat; Rahman, Md Mukhlesur (University Heart Journal, 2019)
Background: Now-a-days primary percutaneous coronary intervention (pPCI) is being increasingly done in our country as the treatment of acute ST elevation myocardial infarction (STEMI). Time until treatment is paramount in the management of STEMI. But the time delay to pPCI how much influencing the outcome in our setting is mostly unknown.So we evaluated the influence of total ischemic time on myocardial reperfusion and short term clinical outcome in patients with STEMI treated with primary PCI. Materials and methods: This prospective observational study was conducted from August 2016 to March 2017in the Department of Cardiology, National Institute of Cardiovascular Diseases (NICVD), Dhaka. Forty-eight (48) acute STEMI patients were selected by purposive sampling based on inclusion and exclusion criteria dividing into two groups as early treatment group (group-A) in whom pain to pPCI time was <6 hours and late treatment group (group-B) in whom pain to pPCI time was 6-12 hours. Angiographic (TIMI flow grade 3 & MBG 3) & short term clinical outcome (MACE, heart failure, major bleeding, minor bleeding, cardiogenic shock, significant arrhythmia, instent thrombosis) were observed and compared between these two groups. Results: The relationship between total ischemic time and 30-day mortality & morbidity were assessed and compared with early and late pPCI group. The overall 30-day mortality rate was 4.2%, heart failure was 6.2%, cardiogenic shock was 4.2%, major bleeding was 2.1% and minor bleeding was 14.6%. Mortality and morbidity were higher in longer ischemic time group than shorter ischemic time group. In multivariate regression analysis, the factors independently influencing the adverse short term outcome were advance age (OR 1.51, 95% CI 1.105 to 4.101, p=0.03), hypertension (OR 2.44, 95% CI 1.102 to 4.281, p=0.02), diabetes mellitus (OR 2.51, 95% CI 1.200 to 4.987, p=0.02), anterior MI (OR 1.38, 95% CI 1.001 to 2.872, p=0.03), multivessel disease (OR 2.35, 95% CI 1.010 to 5.371, p=0.02), pain to door time (OR 1.66, CI 1.099 to 2.2.722, p=0.04), and total ischemic time (OR 2.67, 95% CI 1.122 to 5.784, p=0.02). Even after correction for predictive baseline and procedural variables of the univariate analysis, longer total ischemic time was the most significant independent predictor (OR 2.67, p=0.02) of short term adverse outcome of primary PCI. The current status of time delay in our country revealed symptom onset to door time was 5.6±2.4 hours, door to balloon time was 1.9±1.1 hours and total ischemic time was 7.3±2.6 hours. Conclusion: According to this study finding, there is prognostic implication of time delay in patients with STEMI undergoing primary PCI. Therefore, all efforts should be made to shorten total ischemic time, including reduction in patient related delays, to improve clinical outcome of STEMI patients. University Heart Journal Vol. 14, No. 2, Jul 2018; 77-82